Torcular Dural Sinus Malformation in the Early Childhood: A Case Report - Islam, Md Shafiqul; Shiplu, Motasimul Hasan; Rana, Md Sumon; Alam, Md Shamsul; Ansari, Ayub; Ashfaq, Musannah; Biswas, Md Shahnawas; Saha, Milton Kumer; Karim, Md Rabiul; Hasan, Mahmudul (Bangladesh Journal of Neurosurgery, 2022)
Arteriovenous malformations (AVM) are rare diseases in pediatric age groups, and dural sinus malformation (DSM) has a lower incidence rate. DSMs are associated with mild male dominance, and onset symptoms appear around 5 months of age. The most common clinical presentation is macrocrania, seizures, psychomotor delay, intracranial hemorrhage, congestive heart failure, and brain ischemia. Early recognition of these lesions is essential to prevent brain injury for ischemia and intracranial hypertension. Case description: We discuss the case of a 8 month-old boy presenting with macrocrania secondary to atorcular dural sinus malformation. This case was successfully treated by the endovascular procedure, reaching the goal of the treatment to obliterate the arterial portion of the fistula while preserving cerebral venous drainage to reduce the pial reflux to prevent venous hypertension and ischemic complications. Bang. J Neurosurgery 2021; 11(1): 41-44